The role of self-efficacy and work engagement on the contextual performance of special guidance teachers - Een Rohaeni; Aulia (Humanitas: Indonesian Psychological Journal, 2024)
This research aims to examine the role of self-efficacy and work engagement on the contextual performance of special guidance teachers in inclusive schools. Participants in this research were 101 special guidance teachers consisting of 86 women, 15 men; 22 people aged <30 years, 87 people aged 30-50 years, and 3 people aged >50 years. The data was collected through three scales, namely the self-efficacy scale, the modified UWES scale, and the contextual performance scale and was analysed using the linear regression technique on SPSS 25.00. The results showed that self-efficacy and work engagement together have a significant relationship to contextual performance with a magnitude of 31.2%. Partially, self-efficacy has a very significant role on contextual performance, with a magnitude of 13, 2%; likewise, work engagement has a very significant role in contextual performance with a magnitude of 16,7%. These results have implications on how organisations may improve special guidance teachers' contextual performance by enhancing their self-efficacy and work engagement.